(untitled) (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2024)
The purpose of this study was to qualitatively analyze the Physics textbook of Grade X published by the Punjab Textbook Board to examine critical thinking development. The document was selected using Purposive sampling techniques and analyzed by qualitative content analysis facilitated by NviVo 12 software. The results uncover that the textbook includes various strategies to develop the critical thinking of the students which includes providing the students hands-on experiences from activities and experiments, providing them the conceptual questions to apply their understanding in new situations, by relating scientific concepts to real-life applications, by providing the solved numerical to develop the problem-solving techniques, by delivering the historical background behind the scientific discoveries which illustrate the scientific process. The textbook has involved such strategies to develop critical thinking skills as well as it manifests that the development of the students’ critical thinking can be increased through active learning, by creating brainstorming situations, making the situation for thinking flexibly, and showing the scientific investigation process. The current study yields meaningful implications for teachers that science education needs a variety of pedagogical approaches rather than traditional chalk and talk to develop the critical thinking.